Keterampilan Pemecahan Masalah Mahasiswa Dalam Pembelajaran Bandul Fisis Menggunakan Model Problem Solving Virtual Laboratory - Sutarno Sutarno; Agus Setiawan; Andi Suhandi; Ida Kaniawati; Desy Hanisa Putri (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to explore pre-service physics teachersÃ¢â¬â¢ problem-solving skills through the implementation of problem solving virtual laboratory (PSVL) model on the concept of simple pendulum. This research has been conducted at a university in Bengkulu in academic year 2016/2017. This research is a quasi experiment with nonequivalent control group design. Subjects were 70 students divided into experimental and control groups. Students of the experimental group follow lab activity using PSVL model, while the control group used the expository virtual lab (EVL) model. StudentsÃ¢â¬â¢ problem-solving skills are explored using problem-solving skills tests. Based on the data analysis, it is found that the improvement of studentsÃ¢â¬â¢ problem solving skills of experimental group and control group differ significantly. Improved studentsÃ¢â¬â¢ problem solving skills in experiment group was higher than control group. It can be concluded that the implementation of the PSVL model can improve studentsÃ¢â¬â¢ problem-solving skills.